Reviving the Past: The Role of Sharia in Preserving Forgotten Customs within Islamic Culture - Putra, Dedisyah; Nasution, Martua; Edi, Sabrun (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Islamic law not only acts as a legal system, but also as an instrument in maintaining cultural identity and maintaining the continuity of tradition in Muslim society amidst the flow of globalization. This study aims to reveal the position of customs in the Islamic legal system. This study uses a qualitative method with a normative and sociological juridical approach. The results of the study found that Islamic law is universal and permanent, while customs are local and dynamic. In customary practices, there are those that are acceptable and in line with Islamic law (úrf sahih) such as customary practices in the implementation of aqiqah and marriage which show that customs can coexist and there are also customary practices that are not in line with sharia principles (úrf fasid) which must be abandoned. The principle of consistent sharia states that customs can be used as a basis for determining laws and this shows that Islamic law has accommodated customary practices that are in line and rejected practices that conflict to ensure that the applicable legal system is in accordance with divine values ​​and upholds dignity and human values and avoid potential conflict between the two.